Pendampingan Peningkatan Kapasitas Petani Melalui Pelatihan Pembuatan Pupuk Organik Cair - Arik Dwijayanto; Khotim Munawir; Muhammad Khoirul Rifai (Abdimas Indonesian Journal, 2023)
This article results from community service through training in making organic liquid fertilizer. This community service activity aims to provide solutions for peaseants in Biting Village, Purwantoro District, Wonogiri Regency, Central Java, for the problem of difficulties in obtaining subsidized chemical fertilizers. This community service activity uses the ABCD (asset-based community-driven development) method to analyze community needs by assisting peaseants in making liquid organic fertilizer from rice washing water (leri) as an alternative to subsidized chemical fertilizers, which are difficult for peaseants to obtain. The results of this community service activity through training in making organic liquid fertilizer show the significance of peaseants being able to make organic liquid fertilizer from materials that are easily obtained so they do not depend on subsidized chemical fertilizers. Apart from that, after training in making organic liquid fertilizer, peaseants can save production costs to allocate the budget for purchasing fertilizer for other primary needs.